Diarrhoeal pathogenesis in Salmonella infection may result from an imbalance in intestinal epithelial differentiation through reduced Notch signalling. (16th February 2022) - Quach, Andrew; Jayaratne, Rashini R.; Lee, Beom Jae; Ibeawuchi, Stella‐Rita; Lim, Eileen; Das, Soumita; Barrett, Kim E.
Abstract : Abstract: Infections with non‐typhoidal Salmonella spp. represent the most burdensome foodborne illnesses worldwide, yet despite their prevalence, the mechanism through which Salmonella elicits diarrhoea is not entirely known. Intestinal ion transporters play important roles in fluid and electrolyte homeostasis in the intestine. We have previously shown that infection with Salmonella caused decreased colonic expression of the chloride/bicarbonate exchanger SLC26A3 (down‐regulated in adenoma; DRA) in a mouse model. In this study, we focused on the mechanism of DRA downregulation during Salmonella infection, by using murine epithelial enteroid‐derived monolayers (EDMs). The decrease in DRA expression caused by infection was recapitulated in EDMs and accompanied by increased expression of Atonal Homolog 1 (ATOH1), the goblet cell marker Muc2 and the enteroendocrine cell marker ChgA. This suggested biased epithelial differentiation towards the secretory, rather than absorptive phenotype. In addition, the downstream Notch effector, Notch intracellular domain (NICD) and Hes1 were decreased following Salmonella infection. The relevance of Notch signalling was further investigated using a γ‐secretase inhibitor, which recapitulated the downregulation in Hes1 and DRA as well as upregulation in ATOH1 and Muc2 seen following infection. Our findings suggest that Salmonella infection may result in a shift from absorptive to secretory cell types through Notch inhibition, which explains why there is a decreased capacity for absorption and ultimately the accumulation of diarrhoeal fluid. Our work also shows the value of EDMs as a model to investigate mechanisms that might be targeted for therapy of diarrhoea caused by Salmonella infection. Key points: Salmonella is a leading foodborne pathogen known to cause high‐chloride‐content diarrhoea. Salmonella infection of murine enteroid‐derived monolayers decreased DRA expression. Salmonella infection resulted in upregulation of the secretory epithelial marker ATOH1, the goblet cell marker Muc2 and the enteroendocrine cell marker ChgA. Downregulation of DRA may result from infection‐induced Notch inhibition, as reflected by decreased expression of Notch intracellular domain and Hes1, as well as from decreased HNF1α signalling. The imbalance in intestinal epithelial differentiation favouring secretory over absorptive cell types is a possible mechanism by which Salmonella elicits diarrhoea and may be relevant therapeutically. Abstract : Abstract figure legend Upon infection of the intestinal epithelium with Salmonella, diarrhoea may be explained by an imbalance of intestinal epithelial differentiation. Downregulation of cell‐fate commitment to the absorptive lineage, as reflected by decreased Hes1 and DRA, was observed. Conversely, upregulation of epithelial differentiation into secretory cell types was observed, as reflected by increased ATOH1, Muc2 and ChgA.